Physicians as Patient Teachers - Brunton, Stephen A. (1984)
Physicians have a central role in educating patients and the public in the elements of personal health maintenance. To be an effective teacher, one must recognize the learning needs of each patient and use methods of information transfer that will result in comprehension and compliance. To bring about a change in life-style, one must also have an understanding of a patient's health beliefs and the determinants of human behavior. Using this information together with behavior modification strategies, physicians can forge an effective partnership with patients working toward the goal of optimum health.